2021
DOI: 10.3892/br.2021.1423
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in serum amino acid profiles in children with attention deficit/hyperactivity disorder

Abstract: The objective of the present study was to evaluate the circulating serum amino acid levels in children with attention deficit/hyperactivity disorder (ADHD). A total of 71 children with untreated ADHD and 31 neurotypical controls aged 7-14 years old were examined. Serum amino acid levels were evaluated using high-performance liquid chromatography (HPLC) with UV-detection. Laboratory quality control was performed with reference materials of human plasma amino acid levels. The obtained data demonstrated that chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A previous study determined the effects of psychostimulants on the metabolome profile in humans [36,37]. Serum samples were used extensively in prior metabolomics studies that investigated the effects of many diseases, such as Parkinson's disease [38], attention deficit/hyperactivity disorder [39], amyotrophic lateral sclerosis [40] and Alzheimer's disease [41]. In the current study, we investigated the effect of chronic exposure to cannabis or amphetamine on the metabolomics profile in the serum of addicted Saudi males.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study determined the effects of psychostimulants on the metabolome profile in humans [36,37]. Serum samples were used extensively in prior metabolomics studies that investigated the effects of many diseases, such as Parkinson's disease [38], attention deficit/hyperactivity disorder [39], amyotrophic lateral sclerosis [40] and Alzheimer's disease [41]. In the current study, we investigated the effect of chronic exposure to cannabis or amphetamine on the metabolomics profile in the serum of addicted Saudi males.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the study conducted on D1CT-7 mice revealed a direct association between Glu release in the CSTC loop and tic disorder behavior ( 136 ). However, elevated levels of serum Glu and Asp have also been found in children with ADHD ( 137 ). And magnetic resonance spectroscopy studies suggest a possible rise in Glu levels in the striatum among children with ADHD, OCD, and autism spectrum disorders (ASD) ( 138 , 139 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also demonstrated that the downregulation of the glutamate receptors (GluR) might contribute to ADHD pathogenesis [ 51 ]. It is described that the behavioral abnormality caused by GluR deficiency may depend on dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%